A pilot randomized controlled study of the mental health first aid elearning course with UK medical students - Davies, E. Bethan; Beever, Emmeline; Glazebrook, Cris (BioMed Central, 2018)
Background: Medical students face many barriers to seeking out professional help for their mental health, including stigma relating to mental illness, and often prefer to seek support and advice from fellow students. Improving medical students’ mental health literacy and abilities to support someone experiencing a mental health problem could reduce barriers to help seeking and improve mental health in this population. Mental Health First Aid (MHFA) is an evidence-based intervention designed to improve mental health literacy and ability to respond to someone with a mental health problem. This pilot randomised controlled trial aims to evaluate the MHFA eLearning course in UK medical students.